The Use of Simulation to Teach Nursing Students and Nurses Caring and Empathy: A Scoping Review - Mohamed Toufic El Hussein; Camila Mushaluk; Giuliana Harvey (Research and Theory for Nursing Practice, 2026)
Background: Caring is central to nursing practice and education. While simulation is an effective modality to support the teaching of both technical and nontechnical skills, its impact on nurses’ and nursing students’ empathy and caring behaviors is less clear. Methods: A scoping review, guided by Arksey and O’Malley, Levac et al., and Joanna Briggs Institute frameworks and reported per Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews, searched CINAHL, PsycInfo, MEDLINE, and Health Source: Nursing/Academic Edition. The inclusion criteria were original research or randomized controlled trial, use of simulated patients, nursing participants, and outcomes related to empathy or caring behaviors. Results: Of the 129 studies, 8 met the criteria (2019–2023). All reported improvements in self-perceived empathy and caring across various study designs. Conclusions: Simulation may enhance empathy and caring, though further research is needed to confirm causality.